The Role of Community Empowerment in Efforts to Prevent Non-Communicable Diseases (PTM): Literature Review - Arina Rizki Fauziah; Jenita Frisilia; Andyka Kawa (Universitas Muhammadiyah Palu, 2025)
The increasing prevalence of non-communicable diseases (NCDs) such as diabetes, hypertension and cardiovascular disease is a major public health challenge in Indonesia. Community empowerment through health promotion by providing education to increase knowledge has become a strategy to support the prevention and control of NCDs independently by the community. This research applies the Systematic Literature Review (SLR) method to assess the role of community empowerment in increasing awareness of non-communicable diseases (NCDs). The SLR method was chosen because it is capable of identifying, researching and compiling a synthesis of relevant evidence obtained from previous research. Research results show that community empowerment has a positive impact, especially in increasing awareness, interest and attention to the importance of health information. With growing awareness, communities are becoming more active in taking preventive measures, making this empowerment an important foundation in building healthier and more resilient communities.